Diazepam withdrawal: effects of diazepam and gepirone on acoustic startle-induced 22 kHz ultrasonic vocalizations - Vivian, J A; Farrell, W J; Sapperstein, S B; Miczek, K A (Psychopharmacology, 1994)
It has proven difficult to demonstrate and study the "anxiogenic" quality of drug withdrawal states in animals. Ultrasonic vocalizations (USV) in response to acoustic startle stimuli have shown promise as a measure of affect and may represent "distress" responses during diazepam withdrawal. Three experiments evaluated the association between USV and "distress" by comparing the effects of diazepam as a prototypic benzodiazepine agonist and the putative anxiolytic gepirone with affinity for 5-hydroxytryptamine (5-HT1A) receptors in naive and diazepam-withdrawn subjects. Adult male Long-Evans rats were exposed to acoustic startle sessions consisting of nine 105 dB and nine 115 dB stimuli. USV at 20-30 kHz were readily emitted during startle and often commenced after the third or fourth stimulus presentation. Acutely, intraperitoneal (IP) administration of diazepam (0.1-3 mg/kg) and gepirone (0.1-1 mg/kg) decreased USV dose-dependently without affecting the startle reflex; gepirone also decreased tail flick latency. Startle-induced USV were also sensitive to the "anxiogenic" effects of withdrawal from diazepam exposure (0, 2.5, 5, 10 mg/kg b.i.d. IP x 5 days). Twenty-four hours after the last diazepam injection, rats were hyperreactive to startle stimuli and doubled their rate of USV over vehicle-treated controls. Gepirone (0.1-1 mg/kg IP), but not diazepam (3-20 mg/kg IP) antagonized the increased rate of USV in rats withdrawn from 10 mg/kg b.i.d. diazepam. Diazepam (2.5-10 mg/kg IP) antagonized the increased rate of USV in rats withdrawn from 2.5 mg/kg b.i.d. diazepam.